Comparing the heliospheric cataloging, analysis, and techniques service (HELCATS) manual and automatic catalogues of coronal mass ejections using solar terrestrial relations observatory/heliospheric Imager (STEREO/HI) Data - Rodriguez,L; Barnes,D; Hosteaux,S; Davies,JA; Willems,S; Pant,V; Harrison,RA; Berghmans,D; Bothmer,V; Eastwood,JP; Gallagher,PT; Kilpua,EKJ; et al. (Solar Physics: a journal for solar and solar-stellar research and the study of solar terrestrial physics, 2022)
We present the results of a comparative study between automatic and manually compiled coronal mass ejection (CME) catalogues based on observations from the Heliospheric Imagers (HIs) onboard NASA’s Solar Terrestrial Relations Observatory (STEREO) spacecraft. Using the Computer Aided CME Tracking software (CACTus), CMEs are identified in HI data using an automatic feature-detection algorithm, while the Heliospheric Imagers Catalogue (HICAT) includes CMEs that are detected by visual inspection of HI images. Both catalogues were compiled as part of the EU FP7 Heliospheric Cataloguing, Analysis and Techniques Service (HELCATS) project (www.helcats-fp7.eu). We compare observational parameters of the CMEs from CACTus to those listed in HICAT, such as CME frequency, position angle (PA), and PA-width. We also compare CACTus-derived speeds to speeds derived from applying geometric modelling to the majority of the HICAT CMEs, the results of which are listed in the HELCATS Heliospheric Imagers Geometric Catalogue (HIGeoCAT). We find that both CACTus and HICAT catalogues contain a similar number of events when we exclude events narrower than 20, which are not included in the HICAT catalogue but are found to be identified by CACTus. PA-distributions are strongly peaked around 90 and 270, with a slightly larger CME frequency northwards of the equatorial plane (particularly for the STEREO-A versions of both catalogues). The CME PA-widths in both HICAT and CACTus catalogues peak at approximately 60. Manually derived speeds from HIGeoCAT and automatically derived speeds by CACTus correlate well for values lower than 1000 km s−1, in particular when CMEs are propagating close to the plane of the sky.